Pendekatan KKN Berbasis Partisipasi dalam Mengembangkan Moderasi Beragama melalui Interaksi Antaragama di Desa Simpang Siguragura, Toba - Fahriza Alyanisa (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The Student Community Service (KKN) program serves as a form of community engagement capable of strengthening religious moderation through a participatory approach. This initiative aims to enhance understanding, tolerance, and interfaith cooperation in Simpang Siguragura Village by conducting interfaith dialogues. The implementation employs a participatory method involving community members, religious leaders, village officials, and KKN students. The activity stages include identifying community needs, coordinating with stakeholders, conducting interactive interfaith dialogues, and evaluating outcomes through participant observation and reflective discussions with participants. The dialogues took the form of discussion forums, experience sharing, and Q&A sessions to foster inclusive communication. Results indicate increased community participation in the dialogues, the establishment of more open communication among religious groups, a reduction in prejudice, and strengthened mutual respect and cooperation within the community. Evaluations also reveal a positive response from participants regarding the dialogues as a means to reinforce religious moderation. Thus, a participatory KKN program proves to be an effective medium for fostering a harmonious, tolerant, and sustainable community life.